José María Eguren and José María Arguedas: The divine poet, the cosmic novelist and the intellectual field - Gonzales Alvarado, Osmar (2023)
The present study seeks to provide elements that help to understand the meaning of the works of Eguren and Arguedas, fundamental authors of the Peruvian intellectual field, in light of their biographical processes, vital paths, placing them in the incipient intellectual field and knowing the relationships they established with their peers, and how they expressed two different paths of incorporation into the Peruvian intellectual field. With an approach from the critical sociology of intellectuals, which relates the biography of both authors, of the subjects of ideas with their reflections or creations with the specific society in which they arise and act.